A Novel Approach to Cardiac Magnetic Resonance Scar Characterization in Patients Affected by Cardiac Amyloidosis: A Pilot Study - Michele Alfieri; Federico Guerra; Carla Lofiego; Marco Fogante; Giuseppe Ciliberti; Fabio Vagnarelli; Alessandro Barbarossa; Samuele Principi; Giulia Stronati; Giovanni Volpato; Paolo Compagnucci; Yari Valeri; et al. (Medicina, 2024)
Background and Objectives: Cardiac magnetic resonance (CMR) imaging has become an essential instrument in the study of cardiomyopathies; it has recently been integrated into the diagnostic workflow for cardiac amyloidosis (CA) with remarkable results. An additional emerging role is the stratification of the arrhythmogenic risk by scar analysis and the possibility of merging these data with electro-anatomical maps. This is made possible by using a software (ADAS 3D, Galgo Medical, Barcelona, Spain) able to provide 3D heart models by detecting fibrosis along the whole thickness of the myocardial walls. Little is known regarding the applications of this software in the wide spectrum of cardiomyopathies and the potential benefits have yet to be discovered. In this study, we tried to apply the ADAS 3D in the context of CA. Materials and Methods: This study was a retrospectively analysis of consecutive CMR imaging of patients affected by CA that were treated in our center (Marche University Hospital). Wherever possible, the data were processed with the ADAS 3D software and analyzed for a correlation between the morphometric parameters and follow-up events. The outcome was a composite of all-cause mortality, unplanned cardiovascular hospitalizations, sustained ventricular arrhythmias (VAs), permanent reduction in left ventricular ejection fraction, and pacemaker implantation. The secondary outcomes were the need for a pacemaker implantation and sustained VAs. Results: A total of 14 patients were deemed eligible for the software analysis: 8 patients with wild type transthyretin CA, 5 with light chain CA, and 1 with transthyretin hereditary CA. The vast majority of imaging features was not related to the composite outcome, but atrial wall thickening displayed a significant association with both the primary (p = 0.003) and the secondary outcome of pacemaker implantation (p = 0.003). The software was able to differentiate between core zones and border zones of scars, with the latter being the most extensively represented in all patients. Interestingly, in a huge percentage of CMR images, the software identified the highest degree of core zone fibrosis among the epicardial layers and, in those patients, we found a higher incidence of the primary outcome, without reaching statistical significance (p = 0.18). Channels were found in the scar zones in a substantial percentage of patients without a clear correlation with follow-up events. Conclusions: CMR imaging plays a pivotal role in cardiovascular diagnostics. Our analysis shows the feasibility and applicability of such instrument for all types of CA. We could not only differentiate between different layers of scars, but we were also able to identify the presence of fibrosis channels among the different scar zones. None of the data derived from the ADAS 3D software seemed to be related to cardiac events in the follow-up, but this might be imputable to the restricted number of patients enrolled in the study.